Development of Green and Clean Processes for Perfumes and Flavors Using Heterogeneous Chemical Catalysis - Malkar, Radhika S.; Yadav, Ganapati D. (Current Catalysis, 2020)
Background: In this review, different heterogeneous catalysts based on acid, base, metal and enzymes are discussed for the synthesis of industrially relevant perfumes and flavor compounds. These molecules are mainly produced by a variety of reaction pathways such as esterification, isomerization, hydration, alkylation, hydrogenation, oxidation, etc. All these reactions are discussed thoroughly for the synthesis of vital aromatic compounds. The review also summarizes various recent technologies applied for designing new catalysts to obtain the maximum yield of the desired product. Overall, this review highlights the green, clean and eco-friendly processes which can be industrially accepted for the synthesis of perfumes, flavors and fragrances. Objective: The objective of the current review was to emphasize on the synthesis of industrially important perfumes and flavor molecules such as α-terpineol, cyclohexyl esters, thymol, raspberry ketone, etc. using heterogeneous catalysts. Results: Three hundred and eight papers are reported in this review, the majority of which are on heterogeneous catalysis for the synthesis of molecules which impart flavor or possess perfumery characteristics. Among all, the preparation of esters is highlighted as they represent an imperative functional group in aroma chemicals. Conclusion: The review confirms the need for heterogeneous catalysis in pollution-free and costeffective synthesis of flavor and perfumery compounds.
Keywords: bases